2017
DOI: 10.1016/j.schres.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Social-cognitive brain function and connectivity during visual perspective-taking in autism and schizophrenia

Abstract: Background Autism spectrum disorder (ASD) and schizophrenia are neurodevelopmental conditions that are characterized by significant social impairment. Emerging genomic and neurobiological evidence has increasingly pointed to shared pathophysiologic mechanisms in the two disorders. Overlap in social impairment may reflect similar underlying neural dysfunction in social-cognitive brain networks, yet few studies have directly compared brain function and communication between those with ASD and schizophrenia. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 41 publications
2
44
0
6
Order By: Relevance
“…Similarly, Eack et al also identified increased ventromedial prefrontal and temporo-parietal junction activity in patients with schizophrenia compared to those with ASD during a visual perspective taking task. 43 These findings are comparable to ours in that we also found opposing patterns of activation between groups in left temporoparietal regions and in the VMPFC, although the latter was only apparent in unmedicated individuals. However, Ciaramidaro et al’s findings also differ from ours in that they identified hyperactivation to a non-intentional stimulus in the schizophrenia group, whereas our findings are limited to explicit social judgments (ie, hyperactivation in the SPD group was not seen in the gender vs baseline analysis).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly, Eack et al also identified increased ventromedial prefrontal and temporo-parietal junction activity in patients with schizophrenia compared to those with ASD during a visual perspective taking task. 43 These findings are comparable to ours in that we also found opposing patterns of activation between groups in left temporoparietal regions and in the VMPFC, although the latter was only apparent in unmedicated individuals. However, Ciaramidaro et al’s findings also differ from ours in that they identified hyperactivation to a non-intentional stimulus in the schizophrenia group, whereas our findings are limited to explicit social judgments (ie, hyperactivation in the SPD group was not seen in the gender vs baseline analysis).…”
Section: Discussionsupporting
confidence: 89%
“…The intraparietal sulcus and the superior temporal sulcus are known to be involved in assessing the intent of others, 63 , 64 although more usually in the context of biological motion perception. Interestingly, increased activity in these regions has been reported in people with schizophrenia compared to controls when making judgments of a nonsocial, but not a social, nature 59 and was also identified as hyperactive in schizophrenia compared to ASD by both Ciaramidaro et al 41 and Eack et al 43 …”
Section: Discussionmentioning
confidence: 94%
“…Eighteen additional studies were not eligible for meta-analysis ( 42 – 59 ). These included 10 functional or morphometric imaging studies that did not provide adequate data for quantitative methods [Chen et al ( 42 ), Ciaramidaro et al ( 43 ), Eack et al ( 45 ), Hirata et al ( 46 ), Katz et al ( 47 ), Mitelman et al ( 49 ), Parellada et al ( 52 ), Pinkham et al ( 54 ), Serrano et al ( 57 ), and Stanfield et al ( 58 )], and 8 additional studies that presented data that was either considered ineligible for inclusion in meta-analyses or evaluated social cognition dimensions that were not investigated in more than 3 independent studies: Corbera et al ( 44 ), Le Gall et al ( 48 ), Ozguven et al ( 50 ) and Pomarol-Clotet et al ( 56 ) presented only qualitative data in abstract form; Ozguven et al ( 51 ) presented only data as minimum-maximum and median values and used non-parametric test statistics that were not suitable for inclusion in the meta-analysis; Pilowsky et al ( 53 ) evaluated false beliefs and deception, and Pinkham et al ( 55 ) evaluated paranoia; finally, Van Lancker et al ( 59 ) only presented auditory emotion perception data, and separately for younger and older children with autism. These studies are all summarized in Table 3 and will not be further analyzed here.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a few studies have compared social cognitive impairments in schizophrenia to those in autism, yielding mixed findings. Specifically, some studies found comparable impairments between individuals with schizophrenia and adults with autism on facial affect recognition and mentalizing. However, others reported that schizophrenia patients showed poorer performance on an auditory affect recognition task, but better performance on a mentalizing task, compared to adults with autism.…”
Section: Nature Of Nonsocial and Social Cognitive Impairment In Schizmentioning
confidence: 99%